Iron Bioavailability of Dates (Phoenix Dactylifera) and Goat Milk and Their Effects on Iron Deficiency Anaemia - Nurul Nadiah Binti Mad Zahir
INTRODUCTION: Iron deficiency anaemia (IDA) is a global health problem. Significant increase was shown in haematological parameters after tested date palm and goat milk (GM) on IDA rats. Therefore, this study will focus on the assessment of iron bioavailability in dates and GM using Caco-2 cell lines and their effects on haematological parameter and iron store in IDA subject. MATERIALS AND METHODS: Ajwa date, Mariami date,GM and goat milk fed Ajwa seed (GMFA) were prepared using in vitro digestion method. The caco-2 cells were harvested and used for analysis, and a standard curve was plotted. A quantitative study was conducted among 57 female adults who having mild IDA and assigned with different feeding regime. Blood samples was taken and analysed for full blood count and iron profile. Statistical analysis was performed to compare pre- and post-treatment. RESULTS: The standard curve showed a linear equation: Ferritin(ng)/protein(mg) = (16.519×bread Fe)+16.255, R2=0.974. Using this equation, the bioavailability of iron from the mixture of Mariami date and GMFA shows the highest (78.01±5.26%). It is followed by Mariami date+GM (61.87±3.70%), Mariami date (49.08±2.54%), Ajwa date+GMFA (45.22±2.39%), Ajwa date+GM (42.56±8.61%), Ajwa date (26.48±1.32%), GMFA (9.19±0.94%) and GM (0.87±1.14%). Significant improvement in the haemopoietic activity was reported after subjects were given with date palm andGM treatment. Date palm treatment shows a significant increment in reticulocyte count, haemoglobin and packed cell volume, while GM treatment shows a significant increment in reticulocyte count, red blood cell vi and haemoglobin. Subjects who consume both date palm and GM show significant increments in reticulocyte count and haemoglobin. Furthermore, a significant improvement in ferritin levels was also observed. DISCUSSION: The study found the iron bioavailability of date palm treatment alone and GM treatment alone was lower than a mixture of date palm and GM treatment. The inclusion of goat’s milk in the diet was proven to increase iron bioavailability, improve haematological parameters and restore iron content. GM is poor in iron content, but it contains a higher soluble protein which favours iron absorption. Apparently, the inclusion of dates in the diet would appear to increase haemoglobin as it is rich in iron and high in iron bioavailability as compared to GM. CONCLUSION: Findings support the hypothesis that date palm and GM is beneficial in IDA. Inclusion of date palm and GM is recommended in the diet. It was also noted that goat milk does not interfere with iron absorption.